Evaluating the Utilisation of the National Credit Act 34 of 2005 to Enhance the Recovery of Distressed Financial Entrepreneurs: Lessons from the United States of America - Chitimira, Howard; Mpofu, Kudzai (Acta Universitatis Danubius. Juridica, 2023)
Debt relief involves various measures and strategies that are designed to alleviate and/or restructure debt obligations of the borrower so as to enhance their capacity to comply with such obligations when they are due. This article assesses the adequacy of Chapter 4 of the National Credit Act 34 of 2005 (NCA) in relation to the recovery processes of businesses operated by natural persons, especially sole proprietorships. Most natural persons operate their businesses as sole proprietorships and/or independent entrepreneurs. Accordingly, financially distressed sole proprietorships businesses should have access to flexible debt relief schemes rather than rigid consumer based credit measures that are stipulated under Chapter 4 of the NCA. The consumer based credit measures in Chapter 4 of the NCA are more favourable to individual consumer debtors than the needs of budding entrepreneurs such as sole proprietorships. In this regard, the South African policy makers should consider adopting possible lessons from Chapter 13 of the United States of America (US) Bankruptcy Code, Pub. L. 95-598, Title 1, 11 U.S.C. 101, 6 November 1978, 92 Stat.2549 (US Bankruptcy Code), especially sections 1301 to 1330, which deals with the adjustment of debts for individuals with regular income.